Wage Indexation and Macroeconomic Stability : The Gray-Fischer Theorem Revisted - Jadresic, Esteban (IMF Working Papers; Working Paper ;, 1996)
Since the seminal papers by Gray (1976) and Fischer (1977) were published, the major theorem of the wage indexation literature has been that indexing wages stabilizes output when shocks are nominal and destabilizes output when shocks are real. This paper reexamines the validity of this proposition taking into account the lags in actual indexation practices in an economy similar to that originally considered by those authors. It shows that in such a setup, wage contracts indexed to lagged inflation tend to destabilize output regardless of whether shocks are nominal or real.